Digital-Literacy as the Predictor of Political-Participation a Survey of University Graduates in DIKhan, KP, Pakistan (Global Journal of Human-Social Science, 2015)
This study examines the impact of digital literacy on student's participation in Political Activism'. The computer, internet and cell phone has given rise to the interactive and participatory role of youth in active politics. Survey approach was adopted for data collection. Data was collected through 'Structured-Questionnaire' constructed using the variables extracted from literature. Questionnaire included 6 Demo-graphic and 6 Research variables (4 Predictors and 2 Criterion) expressed through 43 questions. First hypothesis was examined through This study will be a role model/ guideline for researchers working in same line of issues. It will provide a local version of the problem thereby helping to design and plan their research projects accordingly.
Keywords: digital-literacy; political-participation; politicalmobility; voting-behaviour